2004
DOI: 10.1128/aac.48.4.1151-1158.2004
|View full text |Cite
|
Sign up to set email alerts
|

CFE-1, a Novel Plasmid-Encoded AmpC β-Lactamase with anampRGene Originating fromCitrobacter freundii

Abstract: A clinical isolate of Escherichia coli from a patient in Japan, isolate KU6400, was found to produce a plasmid-encoded ␤-lactamase that conferred resistance to extended-spectrum cephalosporins and cephamycins. Resistance arising from production of a ␤-lactamase could be transferred by either conjugation or transformation with plasmid pKU601 into E. coli ML4947. The substrate and inhibition profiles of this enzyme resembled those of the AmpC ␤-lactamase. The resistance gene of pKU601, which was cloned and expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 41 publications
0
42
0
Order By: Relevance
“…A multiplex PCR technique was used to detect plasmid-mediated ampC genes, including bla CMY , bla MOX , bla DHA , bla ACC , bla ACT , bla FOX , and bla CFE (26,27). The PCR-NheI method was used to discriminate between bla SHV-ESBL and bla SHV-non-ESBL genes (28), and nucleotide sequencing of bla SHV was performed for isolates with inconsistent results of genotyping and phenotyping.…”
Section: Methodsmentioning
confidence: 99%
“…A multiplex PCR technique was used to detect plasmid-mediated ampC genes, including bla CMY , bla MOX , bla DHA , bla ACC , bla ACT , bla FOX , and bla CFE (26,27). The PCR-NheI method was used to discriminate between bla SHV-ESBL and bla SHV-non-ESBL genes (28), and nucleotide sequencing of bla SHV was performed for isolates with inconsistent results of genotyping and phenotyping.…”
Section: Methodsmentioning
confidence: 99%
“…Some bla genes have been revealed to associate with mobile insertion sequences such as IS26 and ISEcp1 (Saladin et al, 2002;Ford & Avison, 2004;Nakano et al, 2004). Detection of insertion sequences IS26 and ISEcp1 associated with b-lactamase genes was performed by PCR analysis (Eckert et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…In Korea (14,26), DHA-, CMY/MOX-, and ACT-1/MIR-1-type enzymes have also been identified, while in the United States (1,17), in addition to the types mentioned above, DHA-, ACT-1/MIR-1-, and FOX-type enzymes have been identified. To date, in Japan, MOX-1 (11), CMY-9 (9,28), , CFE-1 (19), CMY-2 (18), and DHA-1 (18) have been found in clinical isolates. Muratani et al (18) reported PABL producers among cephem-resistant K. pneumoniae isolates, but this report did not indicate the rate of occurrence of PABLs.…”
mentioning
confidence: 99%